Carer Appraisal Scale: Second Edition of a Novel Carer-Based Outcome Measure. (April 2020) - Jeyasingam, Neil; Ip, Vincent; Alcock, Hannah; Choi, Sophia Yoon-Young; Lye, Joshua; Perry, Rebecca
Carers are known to have valuable information regarding patient functioning. It has been repeatedly cited that failure of communication between mental health services and the carers of patients is related to critical incidents and failures in patient care. Despite this, there are no structured interventions for carers to participate in patient care, let alone assist with measuring patient progress. This study builds upon and expands on a previous pilot study of a similar measure that was developed for a specific old-age population to create one suitable for general adult use. Development of the Carer Appraisal Scale was based on a grounded theory approach, beginning with semi-structured interviews with staff members working in the mental health service of a major tertiary referral center, with intent on refinement by focus groups, carer feedback, and eventual reduction in total number of items via factor analysis in order to create an accessible and brief measure suitable for regular clinical use. It is proposed that this measure provides additional value for services in engaging the carers of patients in a clinically meaningful way that will greatly impact on patient care.